Analysis of the trends of the development of the role of private local banks and foreign in the Iraqi economy for the period 2003-2014 - Obeyd, Salah Ramadhan; Zaher, Abdul Hamid S. (Humanities Journal of University of Zakho, 2018)
The research relied on the inductive method to reach all of results from partial introductions through the economic analysis of the available data in publications of the government institutions related to the Iraqi banking sector, such as the Central Bank and the Ministry of Planning. The research reached a number of results, the most important of which: The Iraqi banking sector suffers from fundamental imbalances in all its credit, deposit and investment activities, despite the government support. In addition to the existence of unfair competition, that led to the monopoly of government banks for banking activity, that is because of the weakness of the banking culture in Iraq on one hand, and the instructions and government laws that forced the individuals and companies in the private and public sector to go to government banks on the other hand. The study also found that, the foreign banks did not play their real role in supporting banking competition and improving the quality of the provided banking services, for a number of reasons, the most important of which were the granted incentives and facilities of the government for the private banks, which led to the facilitation of banking achievements of the profits in easy ways without presenting real banking services. The study suggests finding ways to encourage private banks to earn profits by providing real banking services instead of relying on government incentives and facilities.